PENGARUH RETURN ON ASSETS, DEBT TO ASSETS RATIO DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - JESSICA ARTAMEVIA; YULIANI ALMALITA (E-Jurnal Akuntansi TSM, 2021)
Purpose of the study is to discover the factors such as return on asset, debt to asset ratio, current ratio, firm size, dividend payout ratio, institutional ownership, tangible asset and company growth that affect firm value of manufacturing companies that listed on IDX during period of 2017 to 2019. Samples used in the study was chosen using purposive sampling method which resulted in 52 manufacturing companies and 156 research data. Data were analyzed using multiple regression analysis. The final result of the study indicate that return on asset has affect positive on firm value because the measurement the level of operational effective and success of the company is based on profitability. Debt to asset ratio has affect positive on firm value because company used the debt to investment so that the price book value of company will be increase, Current ratio has affect positive on firm value because liquidity projecting capability company to pay debt and interest on time. Tangible asset has affect positive on firm value because company can prove their performance with increases their assets. Meanwhile firm size, dividend payout ratio, institutional ownership and company growth have no affect on firm value.